Similarities of Antimalarial Resistance Genes in Plasmodium Falciparum Based on Ontology - Dinar Munggaran Akhmad; Yeni Herdiyeni; Etih Sudarnika (Universitas Ahmad Dahlan, 2018)
The finding of P. falciparum chloroquine resistance (pfcrt) and P. falciparum multidrug resistance 1(pfmdr1) gene in P. falciparum has become an obstacle in treating malaria. The polymorphism between the two genes may result in molecular functions, in cellular components, or in biological processes. The objective of this research is to find similarities between the two genes in 3 components; cellular components, molecular functions and biological processes, based on Gene Ontology. the similarity will be counted semantically by path length approach with Wang method. The range of similarity values is 0-1. After the similarity value examined; in Molecular Function the similarity is 1 due to the same drug transmembrane transporter activity, in Cellular Component is 0,714, the similarity only at the same vacuole food cells, and in Biological Processes is 1 due to the same proces in responding to drug. Therefore, this research proves both genes have similarities based on gene ontology.